Childhood Trauma Affects Stress-Related Interoceptive Accuracy - Schaan, Violetta K.; Schulz, André; Rubel, Julian A.; Bernstein, Michael; Domes, Gregor; Schächinger, Hartmut; Vögele, Claus (Frontiers in Psychiatry, 2019)
Early life adversity (ELA) may cause permanent disturbances in brain-body signaling. These disturbances are thought to contribute to physical symptoms and emotional dysregulation in adulthood. The current study investigated the effects of childhood trauma on young adults’ interoceptive accuracy as an indicator of brain-body communication that may be dysregulated by ELA. Sixty-six participants completed an online-questionnaire followed by a laboratory session including the socially-evaluated cold pressor stress test during which ECG, salivary cortisol and interoceptive accuracy were assessed. Childhood trauma was negatively related to interoceptive accuracy (IAc) after the stressor. This stress-effect could not be observed for heart rate and cortisol, which were unrelated to IAc. Participants reporting higher baseline unpleasantness exhibited lower IAc after the stressor, while increases in unpleasantness due to the stressor were associated with higher IAc. Unpleasantness at baseline mediated the effect of childhood trauma on IAc after the stressor.